Distribuição de macrófitas aquáticas em relação a um gradiente ambiental na bacia do Rio Itanhaém, SP - Mori, Gisele Biem [UNESP] (2014)
Environmental gradients have been widely used as an ecological framework to understand the dynamic and functioning of ecosystems. Watersheds show a different aspect because of the connectivity of rivers and streams in the drainage network, as proposed in the River Continuum Concept (RCC). The aquatic macrophytes, an important component of the aquatic flora, respond to environmental characteristics that influence their occurrence and distribution. In this study we verify the presence of an environmental gradient of abiotic characteristics and macrophytes distribution in a river’s stretch in the Itanhaém river basin, São Paulo, in order to understand if it can be explained by the RCC; and verify which abiotic characteristics are more important in the occurrence of species of aquatic macrophytes. The sampling was realized in downstream-upstream direction in 51 sampling points (500 meters of distance between them) of abiotic variables (limnological and of the channel) and occurrence of the species was determinate by the presence and absence of them in the points. The species of the study were: Egeria densa, Cabomba furcata, Potamogeton pusillus, P. polygonus, Utricularia foliosa, Pistia stratiotes e Salvinia molesta.The abiotic variables and the species occurrence were analysis in scatterplots in relation to the distance between the sampling points to verify the presence of the gradient along the stretch and were adjusted in linear models. The importance of abiotic variables for species occurrence was analyzed by Generalized Linear Models (GLM). To verify the importance of the group of variables in the community was realized a Partial Redundancy Analysis (pRDA). Our results showed that the stretch presents an environmental gradient of abiotic characteristics and species distribution as proposed by the RCC. Egeria densa and C. furcata were the more abundant species and were related to total phosphorus of the substrate, channel depth and...